2007
DOI: 10.1002/ijc.22355
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of HPV‐DNA, p16 and EGFR expression to predict prognosis in oropharyngeal cancer

Abstract: Molecular prognostic indicators for oropharyngeal squamous cell carcinoma (OSCC), including HPV-DNA detection, epidermal growth factor receptor (EGFR) and p16 expression, have been suggested in the literature, but none of these are currently used in clinical practice. To compare these predictors, 106 newly diagnosed OSCC for the presence of HPV-DNA and expression of p16 and EGFR were analyzed. The 5-year disease-free survival (DFS) and overall survival (OS) were calculated in relation to these markers and a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
363
5
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(409 citation statements)
references
References 70 publications
35
363
5
6
Order By: Relevance
“…In this study, we found an HPV prevalence of 24.3% in our cohort, which is lower than the prevalence in OSCC and tonsillar cancer reported for the USA (45-83%) 4,5 or northern Europe (26-93%), 5,23,24 but comparable to data for central Europe (14-33%) [25][26][27] . We considered HPV-association of samples when high risk HPV-DNA was detected along with p16INK4a expression.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, we found an HPV prevalence of 24.3% in our cohort, which is lower than the prevalence in OSCC and tonsillar cancer reported for the USA (45-83%) 4,5 or northern Europe (26-93%), 5,23,24 but comparable to data for central Europe (14-33%) [25][26][27] . We considered HPV-association of samples when high risk HPV-DNA was detected along with p16INK4a expression.…”
Section: Discussioncontrasting
confidence: 69%
“…5,7,[14][15][16] HPV-negative tumors, in contrast, often show inactivation of p16 INK4A , p53 overexpression as a result of gene mutations, cyclin D1 gene amplification and overexpression, as well as EGFR accumulation. 3,[17][18][19] The literature, however, shows conflicting data with respect to HPV-associated characteristics and clinical outcome of head-and-neck squamous cell carcinomas. First, although many studies describe a significant association between HPV presence and favorable prognosis, some studies did not find such a correlation.…”
mentioning
confidence: 99%
“…3 Greater than 86% of HPV-positive tumors over express p16 INK4A (p16), a cyclin-dependent kinase inhibitor, and only 3% of HPV-negative tumors over express p16. 5 Malignant transformation of HPV-induced malignancies involves the E6 and E7 oncoprotein pathways, which functionally inactivate 2 human tumor-suppressor proteins, p53 and pRb, respectively, leading to cellular proliferation, loss of cell cycle regulation, impaired cellular differentiation, increased frequency of spontaneous and mutagen-induced mutations, and chromosomal instability. [5][6][7] Patients with HPV-positive OPSCC reportedly have a better prognosis than patients with HPV-negative OPSCC.…”
mentioning
confidence: 99%
“…5 Malignant transformation of HPV-induced malignancies involves the E6 and E7 oncoprotein pathways, which functionally inactivate 2 human tumor-suppressor proteins, p53 and pRb, respectively, leading to cellular proliferation, loss of cell cycle regulation, impaired cellular differentiation, increased frequency of spontaneous and mutagen-induced mutations, and chromosomal instability. [5][6][7] Patients with HPV-positive OPSCC reportedly have a better prognosis than patients with HPV-negative OPSCC. [8][9][10][11] In a prospective clinical trial by Fakhry et al, it was reported that patients who had HPV-positive OPSCC had a 95% overall survival rate at 2 years compared with a rate of 62% for patients who had HPV-negative disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation